Cyber law in Bangladesh - Karim, Mohammad Ershadul; Blanpain, R. (Roger), 1932-2016; Hendrickx, Frank (Alphen aan den Rijn : Wolters Kluwer Law International, 2022)
Derived from the renowned multi-volume 'International Encyclopaedia of Laws', this practical guide to cyber law - the law affecting information and communication technology (ICT) - in Bangladesh covers every aspect of the subject, including intellectual property rights in the ICT sector, relevant competition rules, drafting and negotiating ICT-related contracts, electronic transactions, privacy issues, and computer crime. Lawyers who handle transnational matters will appreciate the detailed explanation of specific characteristics of practice and procedure.00Following a general introduction, the book assembles its information and guidance in seven main areas of practice: the regulatory framework of the electronic communications market; software protection, legal protection of databases or chips, and other intellectual property matters; contracts with regard to software licensing and network services, with special attention to case law in this area; rules with regard to electronic evidence, regulation of electronic signatures, electronic banking, and electronic commerce; specific laws and regulations with respect to the liability of network operators and service providers and related product liability; protection of individual persons in the context of the processing of personal data and confidentiality; and the application of substantive criminal law in the area of ICT.
"This book was originally published as a monograph in the International Encyclopedia of Laws/Cyber Law."
Includes bibliographical references and index.
SOL
Hye Trade International
Keywords: Computer networks -- Law and legislation -- Bangladesh; Internet -- Law and legislation -- Bangladesh; Electronic commerce -- Law and legislation -- Bangladesh; Law